Effect of tin coating thickness on tin whiskers formation and growth - Yusof, Siti Zahira (2014)
The effect of various thicknesses of tin coating towards tin whiskers formation and growth in 30°C/60%RH environmental condition had been studied. Electroless plating method was used to coat a layer of tin onto copper, Cu substrates. Three different thicknesses were obtained by controlling the plating times of immersion tin. 8 minutes, 12 minutes, and 20 minutes of plating times produced 1.2μm, 1.5μm, and 2.3μm thickness of tin coating respectively. After storage time up to twelve weeks under 30°C/60%RH environmental condition, it was found that the length of tin whiskers in thinnest tin coating (1.2μm) is 48.96pm, followed by 54.24μm in thicker tin coating (1.5μm), and the longest tin whiskers was recorded as 58.58μm in thickest tin coating (2.3μm). Based oil the results, it was clearly shows that the thickness of tin coating affects the growth of whiskers as the thickest tin coating promotes longest whiskers compare to the thinnest tin coating.